Oral health status, behavior and impact profile among naval personnel in the Malaysian naval armed forces - Nik Madihah Nik Azis; Raja Noreihan Raja Abdullah; Mohamad Nur Adzmi Mohamad Ayub; Badiah Baharin (BMC Oral Health)
Abstract Background The oral health of military personnel is critical in ensuring their operational readiness and overall health. This cross-sectional study aimed to assess the oral health parameters, behaviours and impact profile among naval personnel stationed at a Malaysian naval base. Methods Participants first underwent oral health examinations to evaluate their plaque scores, bleeding scores, Community Periodontal Index of Treatment Needs (CPITN), and Decayed, Missing, and Filled Teeth (DMFT) index. Additionally, the oral health behaviours and oral health impact profiles of the participants were assessed through a structured questionnaire. Results A total of 176 naval personnel participated in the study. Overall, the findings indicate high levels of plaque (30.7%) and bleeding scores (39.6%) while the CPITN results showed a significant proportion of participants (52.1%) requiring advanced periodontal treatment (CPITN 3 or 4). The DMFT index highlighted a substantial burden of dental caries with a mean score of 4.59 ± 4.24, including untreated decay (1.15 ± 1.63). The assessment of oral health-related quality of life using the OHIP-14 revealed low scores among some participants, with a mean of 13.47 and a maximum score of 42. Additionally, oral health behaviours were generally inadequate, with 12% of participants reporting infrequent brushing and 68.2% indicating limited use of interdental aids. Conclusions Oral diseases were highly prevalent among the selected population, with notable deficiencies in oral health behaviours such as toothbrushing frequency, the use of interdental cleaning aids, and tongue cleaning. Oral health issues also significantly impacted daily life, as evidenced by the OHIP-14 scores. These findings highlight the need for tailored oral health interventions within the naval setting to enhance deployment readiness, improve oral health outcomes, and elevate the quality of life for naval personnel. Clinical trial number Not applicable.